Gamifying English Language Learning in Non-Language Majors: A Case Study of Kahoot! In Higher Education - Aryawira Pratama; Hadiyanto Hadiyanto; Eddy Haryanto; Bunga Ayu Wulandari; Fauzan Sulman; Desti Anggraini; Retno Wulan (AL-ISHLAH: Jurnal Pendidikan, 2025)
In higher education, English language learning for non-language majors often suffers from low motivation and engagement, particularly among students with analytical academic backgrounds such as Mathematics Education. Gamification has emerged as a promising approach to enhance joyful learning experiences in such contexts. This qualitative case study explores the impact of gamification, using the Kahoot! platform, on the English learning experience of Mathematics Education students at an Indonesian university. Four students were purposively selected from two classes—two high performers and two low performers—to reflect diverse learning experiences. Data were collected through semi-structured interviews and analyzed using iterative coding and thematic interpretation. Findings reveal that game elements such as points, leaderboards, time limits, and answer streaks significantly increased student motivation and active participation. Students reported enhanced cognitive focus, reduced anxiety, and positive emotional responses, including enjoyment and increased confidence. The anonymity feature in Kahoot! contributed to a psychologically safe classroom environment, encouraging risk-taking and collaboration. Additionally, repetitive quiz formats and immediate feedback supported vocabulary acquisition, grammar understanding, and long-term retention. The study concludes that gamification, when applied thoughtfully, can transform English language learning into a more joyful, inclusive, and cognitively enriching experience for students in non-language disciplines. It fosters emotional comfort, strengthens engagement, and improves learning outcomes.